Low-voltage electrical installations in medical buildings - clinical centres and hospitals - Simić Ninoslav (Zbornik Radova: Elektrotehnički Institut "Nikola Tesla", 2015)
This paper presents the observations collected during the testing of electrical installations in medical buildings. The details of the power supply, wiring systems and the implemented systems of protection against electric shocks are described. The causes of some faults during the exploitation of the facilities are presented through practical examples, and the specific problem caused by water leaking through the insulation of electrical installations is explained in detail. It is pointed out how important maintenance, monitoring and application of the latest standards in this area are, as well as adequate training of professional staff.